Blending Pendagogy and Technology: How Digital Tools Enhance Teaching and Learning Outcomes - Sari, Wardani Purnama; Putra, Febi Nuris; Razak, Faisal (Journal of Educational Teaching and Trends, 2025)
The increasing use of digital tools in education has revolutionized teaching practices, yet comprehensive evidence of their educational impact remains limited. A 2023 UNESCO report reveals that while 78% of classrooms now employ educational technology, only 32% of educators receive sufficient training to implement these tools effectively. This discrepancy emphasizes the importance of examining how technology can truly enhance learning when properly integrated with pedagogical methods. This study investigates the effects of pedagogically-informed technology use on student achievement, identifying the most effective combinations of digital resources and teaching approaches across various educational settings. Employing a mixed-methods design, the research analyzed 185 studies (2018-2023) from major databases, along with classroom observations across 15 nations. Qualitative insights from 250 educators revealed implementation challenges. Three key factors emerged as crucial for success: teacher expertise in technology-enhanced pedagogy (β=0.63), curriculum integration (β=0.57), and student digital competence (β=0.49). The results underscore that meaningful educational technology integration requires deliberate pedagogical design, not merely technological access, highlighting the critical need for professional development focused on pedagogical-technological knowledge.